Characterization of Vibrio cholerae non-O1 serogroups obtained from an outbreak of diarrhea in Lima, Peru - DALSGAARD, A; ALBERT, M. J; TAYLOR, D. N; SHIMADA, T; MEZA, R; SERICHANTALERGS, O; ECHEVERRIA, P (Journal of clinical microbiology, 1995)
In February 1994, an outbreak of diarrhea caused by non-O1 Vibrio cholerae occurred among volunteers in a vaccine trial study area in Lima, Peru. Clinically, 95% of the patients presented with liquid diarrhea with either no or mild dehydration. Serogrouping of 58 isolates recovered from diarrheal patients affected in the outbreak revealed seven different serogroups, with serogroups O10 (21%) and O12 (65%) being predominant. Most of these isolates were susceptible to a variety of antimicrobial agents. None of the 58 isolates hybridized with a DNA probe previously used to detect the gene encoding the heat-stable enterotoxin NAG-ST or produced cholera toxin as assessed by GM sub(1) ganglioside enzyme-linked immunosorbent assay. Ribotyping exhibited 10 different BglI ribotype patterns among the 58 V. cholerae non-O1 strains studied. However, ribotyping showed that all isolates belonging to serogroup O12 exhibited identical ribotypes and that 83% of the serogroup O10 isolates belonged to another identical ribotype, thus showing excellent correlation between ribotypes and serogroups. Among a group of O10 and O12 isolates selected for virulence studies, none produced enterotoxin whereas the majority produced a cytotoxin, as assessed in Y1 and HeLa cells. These isolates were also negative for the gene encoding zonula occludens toxin (Zot) as assessed by a PCR assay. The isolates tested showed strong adherence and some degree of invasion in the HEp-2 cell assay, whereas none of the isolates was positive in the PCR assay for the gene encoding the toxin coregulated pilus subunit A antigen (tcpA). In the removable intestinal tie adult rabbit diarrhea model, O10 and O12 serogroup isolates produced severe diarrhea and occasionally death when rabbits were challenged with 10 super(10) bacterial cells. Fluid accumulation was shown in the rabbit intestinal loop test when whole cultures were injected. No significant difference in virulence was shown between serogroup O10 and O12 isolates. This study provides further evidence that V. cholerae non-O1 non-O139 strains have diarrhegenic potential for humans through a yet-undefined mechanism(s) and that such strains can cause outbreaks.